Interior design using virtual reality technology - Tay, Joanne Su Yi (2018)
Design prototyping is a crucial process in the field of interior design to ensure that design ideas are conveyed effectively from designer to customer. Yet, computer-generated 3D renders traditionally provided as mock designs for interior design are captured from a single virtual camera source, which cannot give a real sense of the depth and distances between objects in the scene. Such renders are also not easily modifiable by customers and are quintessentially a one-way communication channel from designer to customer. In view of such drawbacks, this project seeks to explore if virtual reality can improve the design prototyping pipeline on these two fronts. The project has two main aims: to enable the creation of interior design prototypes with an added degree of physical immersion unachievable by traditional renders; and to allow customers to contribute more actively to the design process by offering them the same capabilities a designer has in engaging in interior designing activities. These objectives will be realised through the development of an interior design system prototype hosted fully within virtual reality. The prototype is to enable users to create a house mesh from a floorplan schematic, fully furnish it with furniture and materials, and to end up with a fully decorated virtual interior. To verify if the system developed can match up to existing forms of prototyping, the output produced by the prototype is compared against that of existing 3D modelling suites with favourable results. It is therefore to be concluded that virtual reality presents itself as a decent platform for interior design work and is one worth exploring in greater depth in the future. Possible future developments may wish to look into collaborative endeavours involving multiple VR users in the same space.